1984
DOI: 10.1038/clpt.1984.119
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin: The pseudosteady-state phenomenon

Abstract: After reaching an apparent steady state, plasma phenytoin (PHT) levels may then undergo inexplicable changes, a phenomenon called " pseudosteady state". We evaluated 13 pseudosteady -state periods in 10 inpatients with complex partial seizures. Eleven of the periods occurred after a change in PHT dosage and two after drug withdrawal. The pseudosteady -state period began 2 to 12 days (means = 5.7 days) after dosage change and lasted 5 to 10 days (means = 6.3 days), during which plasma PHT levels were stable (+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Evidence that PHT kinetics may fit a multicompartment model [23) also implies that binding changes may not have a clinically significant effect on drug distribution [b]. Monks and Richens {l6} suggested that rapid diffusion of free PHT into a moderately large volume of distribution and increased hepatic metabolism of unbound drug would minimize plasma level fluctuations resulting from binding variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that PHT kinetics may fit a multicompartment model [23) also implies that binding changes may not have a clinically significant effect on drug distribution [b]. Monks and Richens {l6} suggested that rapid diffusion of free PHT into a moderately large volume of distribution and increased hepatic metabolism of unbound drug would minimize plasma level fluctuations resulting from binding variability.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical considerations suggest that distribution of PHT, with a low drug-protein complex association constant, may be less affected by protein binding than by the ability to penetrate the blood-brain barrier, tissue solubility and binding, and mechanisms of metabolism and excretion [9, 13,221. Evidence that PHT kinetics may fit a multicompartment model [23) also implies that binding changes may not have a clinically significant effect on drug distribution [b]. Monks and Richens {l6} suggested that rapid diffusion of free PHT into a moderately large volume of distribution and increased hepatic metabolism of unbound drug would minimize plasma level fluctuations resulting from binding variability.…”
Section: Discussionmentioning
confidence: 99%
“…The literature of the mid-1980s applied the term "pseudo-steady-state" to phenytoin pharmacokinetics ( 50 ). This term implied that a person was at steady-state or equilibrium with phenytoin, but in reality was not.…”
Section: Fola1e Depletion: "Pseuno-sjeady-staje" Of Phenytoin Pharmacmentioning
confidence: 99%